Management of Feline Hyperthyroidism and the Need to Prevent Oxidative Stress: What Can We Learn from Human Research? - Alessia Candellone; Vittorio Saettone; Paola Badino; Flavia Girolami; Elisabetta Radice; Domenico Bergero; Rosangela Odore; Giorgia Meineri (MDPI AG, 2021)
Feline hyperthyroidism is a clinical syndrome related to an excessive production of thyroid hormones, and it is considered as a spontaneous animal model for human thyrotoxicosis. Many shared features between the feline and the human disease have been identified so far, including pathogenesis, clinical signs, and treatment options. Although methimazole is considered the first-choice drug in both species, several side effects have been described. Furthermore, methimazole could interfere with the oxidative status, already perturbated by the disease. It has been reported in humans that dietary management, mainly through antioxidant supplementation, could mitigate this oxidative burden. The purpose of the review is to describe current therapeutic options in the course of feline hyperthyroidism and to summarize the state of the art relationship between dietary antioxidants administration and the reduction of methimazole side-effects in humans to support the use of this approach also in cats.